2001
DOI: 10.1381/096089201321336647
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancies after Adjustable Gastric Banding

Abstract: Pregnancy in morbidly obese women soon after adjustable gastric banding may occur unexpectedly during a period of weight loss. Prophylactic fluid removal from the band eliminates the efficacy of the obesity treatment. Moreover, this cohort shows an increased incidence of spontaneous abortions and band-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
23

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 17 publications
2
37
1
23
Order By: Relevance
“…Also, port site infection has been reported to be the first symptom of erosion, 22 as seen in some of our patients (Table 1). Although 1 study (23 pregnancies in a series of 359 patients) reported that pregnancy after adjustable gastric banding was not associated with severe complications, 23 band migration after pregnancy has occurred in other studies, 24,25 and severe vomiting in early pregnancy has been hypothesized to be the cause of band migration. 25 Two of our patients (no.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Also, port site infection has been reported to be the first symptom of erosion, 22 as seen in some of our patients (Table 1). Although 1 study (23 pregnancies in a series of 359 patients) reported that pregnancy after adjustable gastric banding was not associated with severe complications, 23 band migration after pregnancy has occurred in other studies, 24,25 and severe vomiting in early pregnancy has been hypothesized to be the cause of band migration. 25 Two of our patients (no.…”
Section: Discussionmentioning
confidence: 94%
“…Although 1 study (23 pregnancies in a series of 359 patients) reported that pregnancy after adjustable gastric banding was not associated with severe complications, 23 band migration after pregnancy has occurred in other studies, 24,25 and severe vomiting in early pregnancy has been hypothesized to be the cause of band migration. 25 Two of our patients (no. 6 and 9) had histories of pregnancy after the LAGB, but we do not know whether vomiting was the cause of migration in these women.…”
Section: Discussionmentioning
confidence: 94%
“…In one series of five pregnancies, all patients required the band to be completely deflated as a result of excessive nausea and vomiting in early pregnancy. 38 Case-control studies comparing patients before and after LAGB have shown a significant reduction in co-mordities. Dixon et al 39 in their study of 79 patients who had LAGB compared with same patients prior to surgery to 79 obese patients and found that there was less maternal weight gain during pregnancy in LAGB patients and that those who became pregnant within one year of surgery gained less weight during pregnancy.…”
Section: Gastric Bandingmentioning
confidence: 99%
“…The American College of Obstetricians and Gynaecologists recommends that to avoid the initial rapid weight loss phase after any such procedure, women should delay pregnancy for 12 to 18 months [11]. However, conception may occur more readily during this stage due to hormonal normalization, so women should be advised to use a reliable form of contraception during this period [71,72].…”
Section: Surgical Management Of Obesity In Women Of Childbearing Agementioning
confidence: 99%
“…Pregnancy after gastric banding has a greater risk of persistent nausea and vomiting. Fluid likely will need to be removed from the band to allow dilation of the gastric opening for reduction of these symptoms [71,72]. However, this may decrease the effectiveness of the treatment and result in weight gain above recommended limits during pregnancy.…”
Section: Surgical Management Of Obesity In Women Of Childbearing Agementioning
confidence: 99%